Quantifying law in police-citizen encounters - Klinger, David A. (Journal of quantitative criminology, 1994)
The way researchers have traditionally measured police action limits their capacity to test legal theories and shed light onto the determinants of law at the initial stage of the criminal justice process. This paper describes extant police action measures and their limitations, offers a new measure that taps variation in the amount of law police officers use in encounters with citizens, presents the results of an analysis that utilizes the new measure, and discusses the implications of this new measure for legal research.